Misja: dziecko. Kobiety i mężczyźni wobec rodzicielstwa i prokreacji - Zygmunt, Agata (Adult Education Discourses, 2020)
The aim of the paper is to presents the results of research on the determinants of reproductive plans and decisions conducted among women and men. The research was carried out in 2016 on a sample of 1,000 inhabitants of the Śląskie Voivodeship, aged 18-39. The survey method was used to conduct them, using the questionnaire interview technique. The presented analyzes are focused on answering questions concerning reproductive plans of women and men, the reasons why they have or want to have children, as well as the effort that they are willing to take in order to implement their plans related to having and raising children. The aim of the comparison of opinions and declarations of women and men at reproductive age is to contribute to the discussion around possible differences in the approach to parenthood and factors determining the decisions on having children. Research results show that having children and being a parent is important for both women and men. However, there are some differences in the reasons why men and women want to be parents. In addition, women are willing to slightly greater sacrifices and efforts aimed at implementing reproductive plans than men.